ENGARUH PROSES BISNIS INTERNAL TERHADAP KINERJA FINANSIAL PADA PERUSAHAAN MINYAK DAN GAS DI PROVINSI RIAU - Basri, Yesi Mutia (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study examines impact internal business process such rework, cycle time andinnovation on financial performance that measured by cost. The study was conducted on theoil and gas companies in Riau Province. Samples in this study are finance manager, HR,production and information systems. Respondents include team leader, team mananajer andcorporate managers. Prior to the first study conducted interviews with key informants toobtain information about performance measurement done. The results of quantitative testingwith Partial Least Square indicate that rework and innovation have positif impact on cost. Inthis study cycle time not has impact on cost and not mediated relationship rework and cost.Keywords: internal business process, rework, cycletime, innovation and cost